2012
DOI: 10.1080/15332861.2012.689565
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Effects of Credibility and Congruency on Consumer Responses to Banner Advertisements

Abstract: This study examined the effects of advertiser credibility and Web site reputation on consumer responses to banner advertisements. In addition, the study investigated the moderating role of productWeb site congruency in determining the effects of the two forms of source credibility on banner ad effectiveness. The results showed that, while advertiser credibility had a significant impact on consumer responses to banner ads, Web site reputation was found to exert no significant influence. Specifically, advertiser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
2
16
1
1
Order By: Relevance
“…Kim and Choi [6] do not offer a definite answer for this issue. They suggest that further research in a variety of settings (e.g., low involvement product) would provide more insights on the role of website credibility in effective banner advertising.…”
Section: Related Workmentioning
confidence: 94%
See 4 more Smart Citations
“…Kim and Choi [6] do not offer a definite answer for this issue. They suggest that further research in a variety of settings (e.g., low involvement product) would provide more insights on the role of website credibility in effective banner advertising.…”
Section: Related Workmentioning
confidence: 94%
“…Kim and Choi [6] examined the effects of advertiser and website credibility on consumer response to banner advertisements. The study failed to show significant effects of website credibility, but they showed significant effects of advertiser credibility on ad credibility, attitude toward the ad, attitude toward the brand and purchase intention.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations